Seroprevalence and asymptomatic carrier status of SARS-CoV-2 in Wuhan City and other places of China. - Shuhui Duan; Meiying Zhou; Wen Zhang; Jianwei Shen; Rui Qi; Xiangrong Qin; Hao Yu; Chuanmin Zhou; Qing Hu; Xue-Jie Yu (Public Library of Science (PLoS), 2021)
Wuhan City (WH) in China was the first place to report COVID-19 in the world and the outbreak of COVID-19 was controlled in March of 2020 in WH. It is unclear what percentage of people were infected with SARS-CoV-2 and what percentage of population is carriers of SARS-CoV-2 in WH. We retrospectively analyzed the SARS-CoV-2 IgG and IgM antibody positive rates in 63,107 healthy individuals from WH and other places of China using commercial colloidal gold detection kits from March 6 to May 3, 2020. Statistical approaches were utilized to explore the difference and correlation for the seropositive rate of IgG and IgM antibody on the basis of sex, age group, geographic region and detection date. The total IgG and IgM antibody positive rate of SARS-CoV-2 was 1.68% (186/11,086) in WH, 0.59% (226/38,171) in Hubei Province without Wuhan (HB), and 0.38% (53/13,850) in the nation except for Hubei Province (CN), respectively. The IgM positive rate was 0.46% (51/11,086) in WH, 0.13% (51/38,171) in HB, and 0.07% (10/13,850) in CN. The incidence of IgM positive rates in healthy individuals increased from March 6 to May 3, 2020 in WH. Female and older age had a higher probability of becoming infected than males (OR = 1.34; 95% CI: 1.08-1.65) or younger age (OR = 2.25; 95% CI: 1.06-4.78). The seroprevalence of SARS-CoV-2 was relatively low in WH and other places of China, but it is significantly high in WH than other places of China; a large amount of asymptomatic carriers of SARS-CoV-2 existed after elimination of clinical cases of COVID-19 in Wuhan City. Therefore, SARS-CoV-2 may exist in a population without clinical cases for a long period.